Correction to: Synthesis, Characterization and Theoretical Study of 1, 2 (2, 2-dihydroxy benzelidenamine) Phenyl Complexes - Najeeb, Dina A; Ahmed, Ahmed; Yusop, Muhammad Rahimi (Al-Nahrain Journal of Science, 2019)
No Abstract.